Surface-Subface Geochemical and Mineralogical Study of Gypcrete in Alexandria Area Central Iraq (Baghdad Science Journal, 2016)
Gypsiferous soil deposits (Gypcrete) are weakly consolidate earthy mixture of secondary gypsum, sand and clay. It is formed in arid and semi- arid area with annual precipitation rainfall less than 400mm. These sediments occur in surface and subsurface in region of little rainfall and rapid evaporation. This research deals with the study of gypcrete in Alexandria to improve the mineralogical and geochemical properties of the gypcrete. The gypcrete soil is used as raw material to produce the plaster for building purposes. Three samples of gypcrete were chemically and geochemically analyzed.The common mineral is howed in 0-0.5m Gypsum followed by Calcite in 0-1m and Quartz in 1-1.5m due to leaching and infiltration by rainfall as well as it full the clay Matrix and the voids between soil constituent, therefore soil properties changes with depth and the clay materials increases such as (Al, Na and K oxides) and Gypsum compound decreases (Ca, S and Sr oxides), yet the change in element concentration, takes the same path. This indicate that annual season rainfall is the only factor affecting mineralogy in this arid area and this means that the Gypsum concentration cannot be affected by ground water either increasing or decreasing. This research concerns about mineralogy and element occurrence variation in this material with accordance to their concentration from surface to depth of 1.5 meter.